Breach of the peace - Ferguson, Pamela R. (Dundee : Dundee University Press, 2013)
Pamela Ferguson describes and critiques the commonly prosecuted crime of 'breach of the peace'. She traces the development of the crime from the mid-19th century to the present day, and also considers related statutory offences. The latter include those offences created by the Criminal Justice and Licensing (Scotland) Act 2010, and the Offensive Behaviour at Football and Threatening Communications (Scotland) Act 2012. It is argued that breach of the peace remains an overly broad and ill-defined crime - despite the appeal court's attempts at narrowing its definition.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Breach of the peace -- Scotland; Law